Pendidikan Paralegal Kepada Masyarakat Sebagai Bentuk Perlindungan Anak Yang Berkelanjutan - Larensius Arliman S (UIR Law Review)
Kids are the future generation, it certainly can not be denied. In any country, the rights of children are always protected and always maintained well. Indonesia as a country of law, also recognizes that child protection must be fully implemented. In these days of child protection seems to be ignored or even forgotten, because we have seen many children are dealing with the law, children are victims of abuse and exploitation, and many children are neglected and attention seriously. On that basis hadirlah paralegal, as an early form to the protection of children. This paper will be acquainted with the paralegal, what is a paralegal? And its development in Indonesia. This paper discusses the benefits paralegal education for the community, especially in the protection of children. At the end of this paper emphasizes the importance of sustainable child protection in Indonesia, as the basis mewudukan Indonesia better. The conclusion of this paper is to introduce a paralegal as an early form of protection to the child sustained.